2008
DOI: 10.1111/j.1365-2966.2008.13483.x
|View full text |Cite
|
Sign up to set email alerts
|

Self-similar structure of magnetized advection-dominated accretion flows and convection-dominated accretion flows

Abstract: We study the effects of a global magnetic field on viscously rotating and vertically integrated accretion discs around compact objects using a self‐similar treatment. We extend Akizuki & Fukue's work by discussing a general magnetic field with three components (r, ϕ, z) in advection‐dominated accretion flows (ADAFs). We also investigate the effects of a global magnetic field on flows with convection. For these purposes, we first adopt a simple form of the kinematic viscosity ν=αc2s/ΩK to study magnetized ADAFs… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
2
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 33 publications
2
2
0
Order By: Relevance
“…By reducing α 2 , the modified viscosity causes the rotational velocity and the sound speed to reduce. Our results in the low-α 2 limit are in good agreement with the findings of Zhang and Dai (2008). They also pointed out that the modified viscosity decreases the radial velocity and the sound speed.…”
Section: Resultssupporting
confidence: 92%
See 2 more Smart Citations
“…By reducing α 2 , the modified viscosity causes the rotational velocity and the sound speed to reduce. Our results in the low-α 2 limit are in good agreement with the findings of Zhang and Dai (2008). They also pointed out that the modified viscosity decreases the radial velocity and the sound speed.…”
Section: Resultssupporting
confidence: 92%
“…( 19)). These results are in excellent agreement with previous work (e.g., Zhang and Dai 2008;Ghoreyshi and Shadmehri 2020;Ghoreyshi 2020). Now, we explore the effects of s on the physical variables of hot accretion flows when η 0 = 0.1.…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…Thus, the effect of other components of the field on the structure of ADAFs must be investigated. The influence of poloidal field component in an ADAF in the absence of outflows has been examined by Zhang & Dai (2008). Adopting the ideal magnetohydrodynamic (MHD) approximation, they concluded that the poloidal field component can reduce the temperature (see also Ghasemnezhad 2017).…”
Section: Introductionmentioning
confidence: 99%